Peritoneal recurrence following nephrectomy for localized renal cancer : A multicenter European real-world analysis of incidence, pattern and treatment (PEMET study–UroCCR 124) - Pettenati, Caroline; Bernhard, Jean Christophe; Khene, Zine Eddine; Capitanio, Umberto; Musso, Giacomo; Albiges, Laurence; Rainho, Larissa; Margue, Gaëlle; Waeckel, Thibault; Verhoest, Gregory; Bento, Lucas; Doumerc, Nicolas; et al. (Urologic Oncology: Seminars and Original Investigations, 2025)
Background: Peritoneal recurrence (PREC) following nephrectomy for localized renal cancer (RCC) is rare. Our objective was to report a multicenter analysis of PREC to analyze incidence, treatment, survival and risk factors. Methods: Between 1987 and 2023, patients with PREC following radical or partial nephrectomy (PN) for localized RCC across ten European institutions (UroCCR, NKI, IRCCS, Foch and Gustave Roussy centers) were included. PREC patterns were defined as isolated PREC (iPREC) and PREC associated with other metastatic sites (mPREC). The main objective was to evaluate PREC incidence (n PREC / n RCC surgeries). Secondary objectives were to assess PREC treatments, patients survival and risk factors associated with iPREC as compared to mPREC. Results: We included 117 patients with PREC, including 35 iPREC (30%) and 82 mPREC (70%). PREC incidence was 0.88%. Compared to mPREC, iPREC was significantly associated with PN (OR 4.1, 95% CI [1.7–9.5], P = 0.001), minimally invasive surgery (MIS) (OR 3.3, 95% CI [1.3–8.2], P = 0.007), and lower Leibovich risk scores (OR 4.6, 95% CI [1.9–11.0], P = 0.001). In multivariable analysis, Leibovich score remained significant (OR 3.3, 95% CI [1.2–8.8], P = 0.016). Treatment was mainly systemic (66.7%). Surgical treatment was performed in 11 iPREC cases, with 10 patients remaining progression-free at a median follow-up of 54 months. Overall survival was significantly better in iPREC group (P = 0.007). Conclusions: PREC incidence was below 1%. Our results suggest 2 distinct mechanisms. One involves local spread, potentially favored by MIS and PN, while the other corresponds to a metastatic dissemination driven by tumor aggressiveness. iPREC appears to have better prognosis as compared to mPREC and be effectively treated with surgery.
Keywords: Carcinosis; Kidney cancer; Metastatic; Peritoneal; Recurrence; Renal cell carcinoma; Surgery